The Environment and Reproductive Health (EARTH) Study: a prospective preconception cohort. Issue 2 (20th February 2018) - Messerlian, Carmen; Williams, Paige L; Ford, Jennifer B; Chavarro, Jorge E; Mínguez-Alarcón, Lidia; Dadd, Ramace; Braun, Joseph M; Gaskins, Audrey J; Meeker, John D; James-Todd, Tamarra; Chiu, Yu-Han; Nassan, Feiby L; et al.
Abstract: STUDY QUESTION: Do environmental exposures, diet and lifestyle factors impact reproductive and pregnancy outcomes among subfertile couples attending a fertility clinic? SUMMARY ANSWER: Environmental chemicals exposure in men and women were associated with reduced fertility and a higher risk of adverse outcomes, whereas some dietary factors improved the probability of successful reproductive outcomes. WHAT IS KNOWN ALREADY: Accumulating epidemiologic evidence has shown associations of environmental chemicals and nutritional factors with reproductive and pregnancy outcomes. However, few studies have been designed to assess these factors simultaneously, and even fewer have collected such data among both men and women in the preconception period. Furthermore, early and sensitive reproductive endpoints (e.g. fertilization, implantation, biochemical pregnancy loss) are largely unobservable in population-based designs. STUDY DESIGN SIZE, DURATION: The Environment and Reproductive Health (EARTH) Study is an ongoing prospective preconception cohort designed to investigate the impact of environmental, nutritional and lifestyle factors in both women and men on fertility and pregnancy outcomes. The study has been ongoing since 2004 and has recruited 799 women and 487 men (447 couples; 40 men joined without female partners) as of June 2017. PARTICIPANTS/MATERIALS, SETTING, METHODS: The study recruits women aged 18–45 years and men aged 18–55 years seeking fertility evaluation and treatment at a large academic hospital fertility center. Women and men are eligible to join either independently or as a couple. Participants are followed from study entry throughout each fertility treatment cycle, once per trimester of pregnancy (for those achieving pregnancy), and up to labor and delivery, or until they discontinue treatment or withdraw from the study. The study prospectively collects a combination of biological samples (e.g. blood, urine, semen), self-reported questionnaire data (including a validated food frequency questionnaire) and medical information abstracted from fertility clinic and hospital records. MAIN RESULTS AND THE ROLE OF CHANCE: Among women in this cohort, higher urinary concentrations of some phthalate metabolites were associated with reduced oocyte yields, lower likelihood of clinical pregnancy, increased risk of pregnancy loss and lower likelihood of live birth following infertility treatment. Certain urinary phthalate metabolite concentrations among men was also associated with decreased odds of implantation and live birth. Maternal soy and folate intake significantly modified the association between bisphenol A (BPA) and IVF outcomes in women. While the EARTH Study has tested many a priori hypotheses, multiple comparisons were undertaken, and we cannot rule out the possibility that some of findings may be spurious or due to chance. LIMITATIONS REASONS FOR CAUTION: While the fertility clinic setting provides the opportunity to measure environmental exposures, diet and lifestyle factors across different windows of vulnerability and to evaluate their potential effect on critical early fertility, pregnancy and delivery outcomes, the findings may be less generalizable to naturally conceived pregnancies. WIDER IMPLICATIONS OF THE FINDINGS: The EARTH Study is one of the few cohorts designed to examine multiple windows of vulnerability, including the paternal and maternal preconception windows and the periconception and prenatal windows, in pregnancy. It is also one of the few human studies that has assessed potential interactions between environmental exposures and dietary factors. STUDY FUNDING/COMPETING INTEREST(S): The EARTH Study has been funded by the National Institute of Environmental Health Sciences since its inception in 2004. The authors declare no competing interests. TRIAL REGISTRATION NUMBER: n/a.